Empowering Indigenous Youth: A Strengths-Based Approach to Positive Development, Relationship Safety, and Community Building ... - Van Bavel, Marisa (Werklund School of Education, 2025)
This dissertation presents three interconnected manuscripts on various aspects of Indigenous youth wellness and the researcher’s journey in community-based research. The first paper (Chapter Two) provides a review of wellness factors that help Indigenous youth thrive. These factors are explored through the lens of the First Nations Mental Wellness Continuum framework. When cultural, social, and historical factors are prioritized, Indigenous youth may find hope, belonging, purpose, and meaning. Further, this review emphasises that culturally rooted initiatives empower Indigenous youth to build on their strengths. In paper two (Chapter Three), I utilized data from the nationally representative General Social Survey: Canadian’s Safety to explore Indigenous youths’ experiences of dating violence. Dating violence represents a manifestation of unhealthy relationship patterns that have emerged from colonial violence. Dating violence was significantly associated with age and gender, along with several social and ...